BJP120: Japanese Language II / Academy of Language Studies - UiTM, Academy of Language Studies (2018)
This is the second of a four part program for Japanese language course. The syllabus ranges from the basic Japanese structures to cultured information. It helps to equip the students with basic communicative competence.